EFEKTIVITAS METODE PEMBELAJARAN AQIDAH DI MA AL-FIKRIYAH PADANG TIJI - Fuad Fuad (SINTESA: Jurnal Kajian Islam dan Sosial Keagamaan, 2020)
The  results titled is Learning The effectiveness of Method Aqeedah At MAS Al-Fikriyah Padang Tiji. This study considered representative for the study because education Aqeedah be one portion of Islamic education provided by educational institutions to students starting from Islamic of elementary school, Islamic of junior high school, Islamic of senior high school synergized in Aqeedah Morals lesson, even to college. To achieve the goal of education is the education Aqeedah must have appropriate learning methods, so that students can learn effectively and efficiently. Therefore, the problems of study are: 1). How learning methods Aqeedah at MAS Al-Fikriyah Padang Tiji. 2). What is the process of learning implementation Aqedah at MAS Al-Fikriyah Padang Tiji. The objectives to be obtained in this study were 1). Describe the learning method Aqeedah at MAS Al-Fikriyah Padang Tiji. 2). Describe the process of implementation of learning Aqeedah at MAS Al-Fikriyah Padang Tiji. This study is a qualitative study, the data collection techniques done is through interview, observation and documentation used by triangulation. The data was analyzed by descriptive analysis. The results of this study indicate that: learning methods Aqeedah at MAN 1 Banda Aceh is done by using the method of group discussion, question and answer, inquiry, lectures, group work, Uswatun Hasanah, training, advice, reward and punishment. The process of learning implementation Aqeedah can run well, it can be seen from the preparation of teachers to teach the material in the material, lesson plan, the method used and of students who have a high spirit as seen in the preparation of students before learning to completion of the learning process, they do so with gusto.